PENGARUH NILAI TUKAR RUPIAH DAN HARGA TERHADAP EKSPOR TEKSTIL DAN PRODUK TEKSTIL (TPT) DI PROVINSI JAWA TENGAH - Vera Pradani Ayuningtyas; Karnowahadi Karnowahadi; Muhammad Nahar (JOBS (Jurnal Of Business Studies), 2015)
The research aims at knowing how impact exchange rate and price of exports of TTP in the province of Central Java to the volume of textile exports of Central Java province. The data collect used a literature review and processed by using multiple linear regression analysis with monthly data year 2006- 2013. Results from this research simultaneous regression test (F Test) showed that the overall free variables studied had a significant effect on the volume of textile exports in Central Java province. Partial regression test (t test) showed that H0 is rejected only in the variable price of textile exports in Central Java (X2), which significantly affects the dependent variable is the volume of textile exports in Central Java Province. While Ha rejected and H0 accepted contained in the exchange rate variable (X1) but not significantly affecting the volume of textile exports in Central Java province